Photometry of the Galactic Cluster NGC 6649 - Pik Sin The; Curt Roslund (Journal of Mathematical and Fundamental Sciences, 1963)
Ichtisar. Dengan mengggunakan teknik fotoelektrik dan fotografik diberikanlah magnitudo dan warna daripada 80 bintang dalam gugus galaktik NGC 6649, dalam UBV Johnson. Dengan menggunakan reflektor 60 intji di Observatorium Boyden telah didapatkan observasi fotoelektrik dalam 3 warna. Untuk fotometri forografik telah diambil katja2 potret dalam 2 warna dengan menggunakan teleskop Schmidt 20-28 intji di Lembang. Modulus djarak visuil semu daripada NGC 6649 adalah 14,2 mag, ekses warnanja ialah 1,2 mag, dan modulus sesungguhnja ialah 10,6 mag., sesuai dengan djarak 1300 parsek. Observasi fotoelektrik membuktikan bahwa salah sebuah bintang dalam NGC 6649 mungkin adalah sebuah bintang berubah Cepheid Abstract. By using photoelectric and photographic techniques magnitudes and colours in the Jhonson UBC system are given for eighty stars in the galactic cluster NGC 6649. Photoelectric three-colour observations were made with the 60 inch reflector at the Boyden Observatory. Photographic plates taken in two colours with the 20-28 inch Scmidht type telescope at Lembang were used for photographic photometry. The apparent visual distance modulus of NGC 6649 is 14.2 mag., the colour excess is1.2 mag. and the true modulus, corresponding to a distance of 1300 parsecs. The photoelectric observation show that one of the stars in the cluster of NGC 6649 is a possible Cepheid variable.